Eigenfunction expansions associated with an operator differential equation non-linearly depending on a spectral parameter - Khrabustovskyi, V. (Methods of Functional Analysis and Topology, 2014)
For an operator differential equation that depends on a spectral parameter in the Nevanlinna manner we obtain expansions in eigenfunctions.